Implementasi Edutainment Untuk Menjadi Guru Idola - Margaretha Sri Sukarti (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: Facts prove that the learning process is fun to boost the academic achievement of students. Subjects deemed difficult it will become easier if the learners have a good emotional bond with his teacher. Even if the teacher had been idolized, learners can tie up verbatim by commas commas spoken teacher.For the implementation of edutainment in the learning process is not negotiable. In this paper we will discuss the implementation of edutainment to become teachers idol. Keywords : edutainment, teacher, students.